ANALISIS BARANG KEBUTUHAN POKOK YANG MENDAPAT FASILITAS PPN DIBEBASKAN - Danny Wibowo (Management and Sustainable Development Journal, 2024)
This study was conducted to determine the efforts of taxpayers in responding to policy changes regarding the grouping of basic necessities into Taxable Goods (BKP). In this case, it is specifically taxpayers who have the status of Taxable Entrepreneurs (PKP) whose businesses are engaged in basic goods or basic necessities. The background of this research is PKP entrepreneurs who are trying to adapt in the midst of intense business competition in the city. In this study using a qualitative approach with interview methods to 5 entrepreneurs as informants from a group of entrepreneurs with PKP status in the Surabaya area. This research shows that the policy on the grouping of basic necessities is determined to be taxable goods, from the administrative side it will increase the burden of the obligation to issue tax invoices for PKP. In addition, input tax that cannot be credited will have an impact on the higher selling price of the product. When product prices rise, people's purchasing power will decrease because demand also decreases. Then it is known that the policy change has several impacts on PKP, which if not balanced with a business strategy can potentially bankruptcy.